Probing built-in stress effect on the defect density of stretched monolayer graphene membranes. (November 2019) - Hu, Kai-Ming; Xue, Zhong-Ying; Liu, Yun-Qi; Song, Peng-Hui; Le, Xian-Hao; Peng, Bo; Yan, Han; Di, Zeng-Feng; Xie, Jin; Lin, Li-Wei; Zhang, Wen-Ming
Abstract: It is of great interest to link Raman scattering to the properties of disorders in graphene membranes, which provides an effective characterization method to probe atomic scale defects. The built-in stress effect on the defect densities of substrate-supported monolayer graphene membranes around wells is investigated. First, a modified phenomenological model is developed to depict the relationship between built-in stresses and defect-activated Raman intensities. To validate the rationality of the modified model, Raman spectroscopy is used to characterize stretched graphene membranes on different patterned substrates with micro-scale wells. The experimental data indicate that the intensity ratio of D mode to G mode ID /IG increases with the Raman test point approaching the well edge. According to the modified model, the increase of ID /IG means the rise of defect densities, which originates from the propagation of initial defects in graphene membranes under built-in tension. The underlying mechanism of defect density increasing phenomenon is that the built-in stresses provide the energy for defect propagations in stretched graphene membranes. Theoretical and experimental comparison well validates the rationality of the modified model. The work can provide a theoretical foundation for Raman characterization method of defect propagations in stretched graphene and applications of defective graphene-based nanodevices.